Concentration and size distribution of atmospheric particles in southern Italy during COVID-19 lockdown period. (15th February 2023) - Conte, Marianna; Dinoi, Adelaide; Grasso, Fabio Massimo; Merico, Eva; Guascito, Maria Rachele; Contini, Daniele
Abstract: Many countries imposed lockdown (LD) to limit the spread of COVID-19, which led to a reduction in the emission of anthropogenic atmospheric pollutants. Several studies have investigated the effects of LD on air quality, mostly in urban settings and criteria pollutants. However, less information is available on background sites, and virtually no information is available on particle number size distribution (PNSD). This study investigated the effect of LD on air quality at an urban background site representing a near coast area in the central Mediterranean. The analysis focused on equivalent black carbon (eBC), particle mass concentrations in different size fractions: PM2.5 (aerodynamic diameter Da  < 2.5 μm), PM10 (Da  < 10 μm), PM10-2.5 (2.5 < Da  < 10 μm); and PNSD in a wide range of diameters (0.01–10 μm). Measurements in 2020 during the national LD in Italy and period immediately after LD (POST-LD period) were compared with those in the corresponding periods from 2015 to 2019. The results showed that LD reduced the frequency and intensity of high-pollution events. Reductions were more relevant during POST-LD than during LD period for all variables, except quasi-ultrafine particles and PM10-2.5 . Two events of long-range transport of dust were observed, which need to be identified and removed to determine the effect of LD. The decreases in the quasi-ultrafine particles and eBC concentrations were 20%, and 15–22%, respectively. PM2.5 concentration was reduced by 13–44% whereas PM10-2.5 concentration was unaffected. The concentration of accumulation mode particles followed the behaviour of PM2.5, with reductions of 19–57%. The results obtained could be relevant for future strategies aimed at improving air quality and understanding the processes that influence the number and mass particle size distributions. Graphical abstract: Image 1 Highlights: Average eBC concentration decreased by 15–20% due to COVID-19 policies. Average concentration of quasi-ultrafine particles decreased by 20%. Long-range transport of dust complicates the estimate of lockdown effect on coarse (PM10-2.5 ) particles. PM2.5 concentration decreased during lockdown but PM10-2.5 concentration was not affected. Large reductions of concentrations of several air pollutants were observed after lockdown.